2013
DOI: 10.1007/s13762-013-0199-y
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of dewatered sewage sludge conditioned with skeleton builders as landfill cover material

Abstract: High water and organic content of sewage sludge constricts its reuse and disposal. It is often necessary to solidify/stabilize the dewatered sludge with solidifying agents before landfill disposal. In this study, the sewage sludge was conditioned with skeleton builders, i.e., fly ash and lime combined with ferric chloride for the purpose of improving the dewatering efficiency. The dewatered sewage sludge was then directly reused as landfill cover materials since the skeleton builders also play a role in solidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The safe disposal of SS has become an important issue affecting sustainable environmental management [5][6][7][8][9] . As an effective method, the solidification/stabilization treatment by mixing into a binder is widely used in the world to realize the resource utilization of SS [10][11][12] .…”
Section: Strength and Microstructure Properties Of Solidified Sewage mentioning
confidence: 99%
See 1 more Smart Citation
“…The safe disposal of SS has become an important issue affecting sustainable environmental management [5][6][7][8][9] . As an effective method, the solidification/stabilization treatment by mixing into a binder is widely used in the world to realize the resource utilization of SS [10][11][12] .…”
Section: Strength and Microstructure Properties Of Solidified Sewage mentioning
confidence: 99%
“…After adding the binder, the solidified waste can undergo a series of physicochemical reactions, which can stabilize the incorporated toxic substances and improve the mechanical property of SS simultaneously [12][13][14][15][16] . Then the physical and chemical properties of the SSS meet the requirements for disposal in a landfill or use in engineering applications, such as for bricks, subgrade and landfill cover 11,[17][18][19][20][21] . Lim 15 reported that the unconfined strength of the solidified sludge by fly ash and loess satisfied the criteria for construction materials, which was above 100 kPa.…”
Section: Strength and Microstructure Properties Of Solidified Sewage mentioning
confidence: 99%
“…Typically, S/S technology for a viable choice was adopted to solve sludge processing and local material shortages, while changing the waste into a valuable resource for utilization as construction materials [12], such as landfill and pavement construction [13][14][15]. Most previous studies mainly concentrated on cement, coal residue, and fly ash [16][17][18] for binders, while ignoring other industrial waste. Ground granulated blastfurnace slag (GGBS) has been claimed to achieve a remarkable performance to stabilize soft soil [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Sewage sludge can be viewed as a resource for land use in agriculture, biomass, and value-added products. (Barnab et al 2009;Garfí et al 2011;Li et al 2014). However, it is necessary to consider residual contaminants when sewage sludge is released into the environment, due to their direct environmental harms or potential risks to the safety of the environment (Heberer 2002).…”
Section: Introductionmentioning
confidence: 99%